Possible role of features of the intestinal microbiome in patients with colorectal cancer as a cause of anastomotic leak - P. V. Kosareva; R. A. Konev; A. P. Godovalov; L. V. Sivakova; E. I. Samodelkin (Бюллетень сибирской медицины, 2023)
Aim. Following the analysis of literature data, to determine significant factors of intestinal obstruction in patients with colorectal cancer.Materials and methods. We analyzed 84 literature sources from the Scopus, Web of Science, Google Scholar, and PubMed databases, as well as open access articles on Google.Results. The predominant causes of anastomotic leaks after operations for colorectal cancer are discussed, the role of the microbiome in the development of postoperative complications is analyzed. The intestinal microbiome of patients with colorectal cancer contains bacteria that are not normally found under physiological conditions. These bacteria contribute to the development of disease, suture failure after surgery for intestinal obstruction, and progression of carcinogenesis. This effect is due to the production of bacterial metabolites, the effect on the human immunity, and competition with obligate intestinal microflora. On the other hand, the use of drug therapy, including antibiotics, leads to mass death of obligate bacteria. Therefore, it is important to search for drugs and treatment methods that, if possible, do not have a significant negative impact on the microbiome, but are capable of destroying pathogenic microorganisms. The concept of Russian authors was proposed, which consists in the intraluminal use of rifaximin-α for the prevention of purulent and septic complications and anastomotic leaks during reconstructive surgeries on the distal colon.